INTRODUKSI PRODUK NILA SALIN PADA DESA MITRA POLITEKNIK KELAUTAN DAN PERIKANAN KARAWANG - Pramono Adi, Catur (Fakultas Pertanian_Universitas Tidar, 2023)
One of the problems that exists among coastal communities in Karawang Regency, especially Tirtajaya District, is that the majority of cultivated land owned by the community is brackish or salty. This causes the diversity of biota types to be cultivated to be limited, so other types are needed. The aim of implementing community service activities in 2023 is: to provide input on innovations in the marine and fisheries sector, especially the fisheries cultivation sector, to community actors or cultivators, with results including: 1. Increased knowledge and skills of the target community in Karawang Regency in aquatic Tilapia Cultivation activities brackish, 2). Implementation of outreach to increase education and motivation among target communities in Karawang Regency in brackish water cultivation businesses, 3). Increasing the competency of members of the Tambaksari community group in cultivating saline tilapia.